Ensino de Geometria: Construção de materiais didáticos manipuláveis com alunos surdos e ouvintes - Santos, Lijecson Souza dos (2018)
Inclusive quality education is an essential condition for the human being, a everyone, but for a long time people with these denied rights, especially the deaf, who are still fighting for equal rights, to recognize their culture and language, the Sign Language. Thus, the present research had as main objective to analyze the results of a didactic sequence applied in a 9th grade class with deaf and hearing students, based on the construction of materials manipulable, verifying their participation in the mediation of the content of Geometry between teacher and the interpreter of Pounds. The field work was carried out in a public school of regular education in the city of João Pessoa - PB, participating 10 students, being 8 hearing students and 2 deaf students. Because we chose to research our classroom, we agree with Lankshear and knobel (2008), who are research is characterized as a pedagogical research. The organization of this research, follow with the assumptions of the didactic engineering methodology, according to Artigue (1996). From the ideas of Raymond Duval (2008) on knowledge the importance of the semiotic representation registers for the acquisition and their contribution to the elaboration, application and analysis of the sequence didactic Vygotsky's theory of learning has provided us with methodologies for the elaboration, application and analysis of the didactic sequence. The results revealed that the manipulative teaching material is a very important ally to the teacher in geometry teaching / learning for deaf students and listeners. Your effectiveness is affirmed with the participation of the teacher and the sign language interpreter, because the material is only a mediating instrument. We also emphasize the importance of their group production by increasing the interaction among these students.